Développement du matériel d’apprentissage en utilisant du media Linktree au SMA Negeri 7 Binjai - Fenni Yunita Frenxia Tampubolon; Hesti Fibriasari (Universitas Negeri Semarang, 2024)
This study aims to develop Situate in Time learning materials based on Linktree media and to determine the feasibility of the developed learning materials. This research uses the research and development (R & D) method of the ADDIE development model which includes five stages, namely analyze, design, develop, implement, and evaluate. In this study, only up to 3 stages, namely, Analysing, Designing, and Developing. This research stage begins with the data collection carried out with the needs analysis. The results showed that up to 68.7% of students had difficulty learning the subject Situate in Time. 18.7% of students responded to learning difficulties with teaching materials, instructions, signs, and panels and 12.6% of students had difficulties with everyday materials. So, to reduce the difficulty of students to learn the time-based material as the material with the highest level of difficulty, 87.5% of students want to learn more. The results showed that the Situate in Time material developed using Linktree media is quite usable as a learning aid. Validation test results from Materials Experts are 83% with Very Good Categories and Media Experts are 94% with Very Good Categories. Based on the results of this validation, Linktree-based learning materials are quite feasible in Set in Time learning materials.